P63 Neural respiratory drive and breathlessness intensity relationships during acute and recovery phases of exacerbations of chronic obstructive pulmonary disease. (December 2018) - Cho, PSP; Fletcher, HV; Patel, IS; Rafferty, GF; Moxham, J; Turner, RD; Birring, SS; Jolley, CJ
Abstract : Introduction: Increased breathlessness is a cardinal symptom of acute exacerbations of chronic obstructive pulmonary disease (AECOPD). Breathlessness intensity is closely related to neural respiratory drive (NRD). However, it has been proposed that airway inflammation, leading to sensitisation of pulmonary C-fibres, may increase breathlessness intensity relative to NRD during AECOPD. We hypothesised that breathlessness intensity, relative to NRD, would be higher during AECOPD than when clinically stable. Methods: Patients hospitalised with a clinician diagnosis of AECOPD were studied during admission (TAECOPD ) and after a 6 week recovery period (TREC ). On both occasions, patients underwent incremental shuttle walk testing to their symptom-limited maximum. Parasternal intercostal muscle electromyogram (EMGpara) recordings were made continuously over the subsequent 10 min recovery period. Modified Borg (mBorg) breathlessness intensity was recorded at each one-minute interval. EMGpara, expressed as a proportion of peak inspiratory EMGpara recorded during maximal volitional manoeuvres (EMGpara%max), was multiplied by respiratory rate to calculate the NRD index (NRDI). NRDI-breathlessness intensity relationships were analysed by applying linear mixed effects model analysis. Results: 12 patients (median (IQR) age 67.5 (55.0–72.8) years, 6 (50%) female, mMRC 3 (2–3), FEV1 41.0 (31.0–56.8)% predicted, length of stay 6 (3–8) days) were recruited. mBorg breathlessness intensity was closely related to NRDI (beta=0.006, p<0.0001) at both TAECOPD and TREC . On both occasions, there was significant inter-individual variability in the covariance (Wald Z=2.189, p=0.029) and intercept (Wald Z=2.201, p=0.028) of the breathlessness intensity and NRDI relationships. However, there was no significant intra-individual difference in the covariance (beta <0.001, p=0.358) or intercept (p=0.095) of the breathlessness intensity-NRDI relationships when TAECOPD and TREC were compared (figure 1). Discussion: Contrary to our hypothesis, we observed no significant differences in the relationship between NRD and breathlessness intensity in COPD patients during an AECOPD when compared to the stable state. This suggests that airway inflammation does not influence the key association between NRD and breathlessness during AECOPD. This emphasises the importance of treatment strategies that reduce the load on the respiratory muscle pump and ventilatory drive to the management of breathlessness in AECOPD.